Analisa Perhitungan Muka Air Rata-Rata Di Lahan Gambut Dengan Tanggul Keliling Dalam Rangka Mengurangi Kebakaran - Indra Setya Putra; Yudi Lasmana (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2019)
Peatland fires encourage the government to restore peat function as natural water storage. One of the measures taken is to build a circumference dike to hold water to reduce excessive drainage. However, there is no study yet of the planned average water level that has to be maintained from the construction of circumference dike. Therefore, the aim of this study is to calculate the average water level on peatlands inside the circumference dike. The methods used consist of hydrological analysis, spatial analysis, and water level analysis. The results of the analysis shows that the average water level in normal years tends to be above the surface, except in the second half of August to the first half of November. In the second half of September to the second half of October, the peat has the potential to be burned. In a dry season the water tends to fall decline to the drainage boundary of peatland which is at -1.5 m which occurs in the second half of March to December. In the second half of February until December peatland has potential to be burned. From this research, it can be concluded that the calculations using this method is similar with in-situ observation data and can be used to calculate the average water level of peat with the same conditions in other locations.